Chromosomal location of resistance to Septoria tritici in seedlings of a synthetic hexaploid wheat, Triticum spelta and two cultivars of Triticum aestivum - Simón, María Rosa (2001)
Chromosomal location of resistance to two virulent Argentinean isolatesofSeptoria triticiwas studied in two wheat (Triticum aestivumL.) cultivars (Cappelle-Desprez & Cheyenne), a synthetic hexaploid(Synthetic 6x) andTriticum speltain seedlings. Substitution lines of these(resistant or moderately resistant) genotypes into (susceptible)ChineseSpringwere selected from a previous screening. For Synthetic 6x,resistance was clearly located in chromosome 7D. Chinese Spring with the7D chromosome substituted by Synthetic 6x showed almost completeresistance, similar to the level of Synthetic 6x. For the substitutions withCappelle-Desprez, Cheyenne, andT.speltathere were no lines with abehaviour similar to the resistant parent. However, some substitutions weremore resistant than the susceptible parent suggesting that severalchromosomes could be involved in the resistance of these genotypes toSeptoria leaf blotch.